Intelligent Systems for Rehabilitation Engineering - Raut, Roshani; Pathak, Pranav; Kautish, Sandeep; N. , Pradeep (Wiley-Scrivener, 2022)
INTELLIGENT SYSTEMS FOR REHABILITATION ENGINEERING Encapsulates different case studies where technology can be used as assistive technology for the physically challenged, visually and hearing impaired. Rehabilitation engineering includes the development of technological solutions and devices to assist individuals with disabilities, while also supporting the recovery of the disabled who have lost their physical and cognitive functions. These systems can be designed and built to meet a wide range of needs that can help individuals with mobility, communication, vision, hearing, and cognition. The growing technological developments in machine learning, deep learning, robotics, virtual intelligence, etc., play an important role in rehabilitation engineering. Intelligent Systems for Rehabilitation Engineering focuses on trending research of intelligent systems in rehabilitation engineering which involves the design and development of innovative technologies and techniques including rehabilitation robotics, visual rehabilitation, physical prosthetics, brain computer interfaces, sensory rehabilitation, motion rehabilitation, etc. This groundbreaking book Provides a comprehensive reference covering different computer assistive techniques for the physically disabled, visually and hearing impaired. Focuses on trending research of intelligent systems in rehabilitation engineering which involves the design and development of innovative technologies and techniques. Provides insights into the role of intelligent systems in rehabilitation engineering. Audience Engineers and device manufacturers working in rehabilitation engineering as well as researchers in computer science, artificial intelligence, electronic engineering, who are working on intelligent systems.